Are Suicide Rates Related to the Psychiatrist Density? A Cross-National Study - Sher, Leo (Frontiers in Public Health, 2016)
Introduction. Most suicide victims have a diagnosable psychiatric disorder. Treatment of psychiatric disorders should reduce the number of suicides. Higher psychiatrist-per-population ratio increases the opportunity for contact between the patient and psychiatrist. It is reasonable to hypothesize that the higher psychiatrist density is associated with lower suicide rates. The aim of this study is to examine the association between suicide rates and the psychiatrist density in the European Union countries. These countries are economically and culturally connected and located on the same continent. This is an attempt to study a relatively homogenous sample. Methods. Correlations were computed to examine relationships between age-standardized suicide rates in women and men, psychiatrist density, and the gross national income (GNI) per capita. Partial correlations were used to examine the relation between the psychiatrist density and age-standardized suicide rates in women and men controlling for the GNI per capita. Results. Higher suicide rates in women correlated with the higher psychiatrist density. Controlling for the GNI per capita, the psychiatrist density positively correlated with suicide rates both in women and in men. There was a trend towards a negative correlation between the GNI per capita and suicide rates in men. The psychiatrist density was positively associated with the GNI per capita. Conclusion. Probably, higher suicide rates directly and/or indirectly affect the decisions made by policy- and lawmakers regarding mental health services and how many psychiatrists need to be trained. The results of this study should be treated with caution because many confounding variables are not taken into account.